(3+2) Cycloadditions of Vinyl Sulfonyl Fluorides with Ethyl Diazoacetate or Azides: Metal-Free Synthesis of Pyrazole and Triazole Scaffolds via SO2 Elimination - Sandeep, K.; Sanjeeva Kumar, A.; Qureshi, Asif Ali; Kumara Swamy, K. C. (Synthesis, 2022)
A (3+2) cycloaddition reaction between substituted vinyl sulfonyl fluorides and ethyl diazoacetate or azides for the rapid construction of pyrazole or triazole cores via Michael addition and SO2 gas elimination is developed. Trimethylsilyl azide or organic azide selectively attacks at the β-carbon of vinyl sulfonyl fluoride rather than at the S(VI) center and generates C-substituted or C,N-disubstituted triazole. In contrast, vinyl sulfonyl fluorides react with ethyl diazoacetate to generate pyrazoles in good to high yields.
Keywords: azides; cycloaddition; diazo compounds; Michael addition; pyrazole; triazole; vinyl sulfonyl fluoride